THE ROLE OF VILLAGE OWNED ENTERPRISES (BUMDES) ON EFFORTS TO INCREASE ORIGINAL VILLAGE INCOME (PADES) AND VILLAGE COMMUNITY WELFARE (CASE STUDY ON TIRTA MANDIRI BUMDES IN PONGGOK VILLAGE, POLANHARJO DISTRICT, KLATEN REGENCY) - Akhmad Abaabiil Alfirdausi; Guntur Riyanto (Journal of Applied Economics in Developing Countries, 2019)
This study uses a mixed approach studies which associates qualitative and quantitative approaches. The qualitative approach in this study will describe the stages of establishing BUMDes, strategies in managing BUMDes, and the benefits of BUMDes on the welfare of the village community. While the quantitative approach will explain the role of BUMDes to increase Village Original Income (PADes). The results of the study showed that the establishment stage of the BUMDes was to recognize the potential of the Village, socialize to the community about BUMDes, create a drafting team, hold a MUSDES, and issue PERDES. The BUMDes strategy in managing its business can be seen from the SWOT factor owned by BUMDes. The benefits of the existence of BUMDes Tirta Mandiri to the community are the many programs offered by the Village to the community, reducing unemployment, and providing assistance to people who want to become entrepreneurs. While the results of quantitative analysis are the highest average sector of Village Original Income (PADes) from the results of the Village business or in this case BUMDes.Keywords: Village, PADes, BUMDes, Ponggok Village